Molecular Diagnosis of Canine Babesiosis with Haemato Biochemical Parameters - Sathish. G; Parthiban. M; Chandrasekar, M; Raja, P; Sesh, P. S. L (The Indian Veterinary Journal, 2023)
The clinical symptoms and pathology of canine babesiosis are similar to those of falciparum malaria in humans, and infections in dogs can result in significant morbidity and fatality. A total of 30 blood samples were collected in MVC clinics from dogs with suspected clinical signs and subjected to estimation of haemato biochemical parameters for detection of thrombocytopenia, anemia and elevated liver enzymes. DNA samples isolated from these blood samples were screened for the presence of B. gibsoni, B. canis canis and B. canis vogeli by PCR. Out of 30, five samples showed positive amplification for B. gibsoni, Four samples showed positive for B. canis vogeli and one sample showed positive for B. canis canis. When comparing the severity of infection, B. gibsoni showed severe anemia and hepatitis than other Babesia spp.